2009
DOI: 10.1002/hep.22916
|View full text |Cite
|
Sign up to set email alerts
|

Statins potentiate the in vitro anti-hepatitis C virus activity of selective hepatitis C virus inhibitors and delay or prevent resistance development #

Abstract: Worldwide approximately 170 million people (or almost 3% of the global population) are chronically infected with HCV. Chronically infected patients are at increased risk of developing liver cirrhosis and hepatocellular carcinoma. 1 In Western countries, infection with HCV is the most common cause of liver transplantation. The current standard therapy for chronic hepatitis C consists of the combination of pegylated interferon alpha (IFN-␣) and ribavirin. This therapy is only effective in 50% to 60% of infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
97
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 39 publications
3
97
0
Order By: Relevance
“…It has been also shown that the combination of statins (except pravastatin) with interferon exhibited strong inhibitory effects on HCV RNA replication [120]. This was the first time when statins, especially fluvastatin, were shown to be potentially useful as new anti-HCV agents in combination with interferon [120], and that was confirmed in other studies [121]. Statin use (especially simvastatin, lovastatin and atorvastatin) in HCV patients is also associated with a 28% decrease in risk of HCC.…”
Section: Hepatitis B (Hbv) and C Virus (Hcv) Liver Diseasementioning
confidence: 77%
See 1 more Smart Citation
“…It has been also shown that the combination of statins (except pravastatin) with interferon exhibited strong inhibitory effects on HCV RNA replication [120]. This was the first time when statins, especially fluvastatin, were shown to be potentially useful as new anti-HCV agents in combination with interferon [120], and that was confirmed in other studies [121]. Statin use (especially simvastatin, lovastatin and atorvastatin) in HCV patients is also associated with a 28% decrease in risk of HCC.…”
Section: Hepatitis B (Hbv) and C Virus (Hcv) Liver Diseasementioning
confidence: 77%
“…The percentage of patients who fail to receive statins because of fear of hepatotoxicity ranges between 10-30% [126]. On the other hand statins contribute to the clearance of viral hepatitis [120][121][122], and substantially reduce the risk of HCC [119,122,123]. Thus, the fear of a possible drug adverse effect, which is extremely rare, might be a reason that many patients needlessly suffer or die from cirrhosis, HCC or CVD events [126].…”
Section: Hepatitis B (Hbv) and C Virus (Hcv) Liver Diseasementioning
confidence: 99%
“…22 Conflicting evidence suggests that the opposite may be true, with less efficient uptake of HCV pseudoparticles (34%) seen in hepatoma cells treated with mevastatin as well as less efficient (48% inhibition) internalization of HCV into cells treated with statins. 20 Clearly, a better understanding of the role of the LDL receptor in HCV infectivity is required, and it is possible that the pleiotropic effects of statins may prove to be more relevant. Evidence suggests that HCV replicates within hepatocytes after an HCV replication complex is formed on lipid rafts within the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that statins may play a role is intriguing. Delang et al 20 showed that statins delay or prevent development of resistance. Another finding of this study is the small number of patients with CHC who were actually on a statin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation